Laser Based Energy Distribution Architecture for Decoupling Energy and Sensing Planes in WSN - Naveed Anwar Bhatti; Affan A. Syed; Muhammad Hamad Alizai (International Journal of Distributed Sensor Networks)
We propose decoupling energy and sensing planes in WSN. This decoupling represents a paradigm shift as it can alleviate the fundamental problem of energy depletion in WSN and can (in theory) offer a sensor network with infinite lifetime. We present energy transference as the mode of decoupling energy by allowing energy to move between energy-rich and energy-poor nodes. We present a first practical energy distribution architecture that allows us to decouple energy supply from sensing activities. Such a separation of responsibilities enables us to utilize abundant energy sources distant from the sensing location, allowing unrestricted lifetime and resolving unequal energy consumption in WSN. We demonstrate energy transfer for practical decoupling using low-cost and low-footprint, laser μ -power beaming that powers current WSN platforms at 100 m of range. We design and implement LAMP, a tiered architecture to manage energy supply to both mesh and clustered WSN deployments using an energy distribution protocol. We evaluate our system to show that, for an additional cost of $29 per mote, LAMP can support perpetual mesh functionality for up to 40 sensors or 120 nodes in clustered operation.